Energy Analysis of Fuel Cell Electric Vehicles (FCEVs) under European Weather Conditions and Various Driving Behaviors1. Issue 5 (18th October 2018) - Hollweck, B.; Moullion, M.; Christ, M.; Kolls, G.; Wind, J.
Abstract: Due to the auxiliary loads' increasing influence on the overall energy consumption of electrified vehicles, a holistic tank‐to‐wheel analysis is necessary. To do so, the impact of the auxiliary load on the energy consumption of a fuel cell electric vehicle (FCEV) drivetrain is investigated by taking different driving behaviors and three European environmental conditions (Spanish, German and Norwegian weather profiles) into account. The driving pattern is analyzed with the study 'Mobilität in Deutschland' [1] and represented with the Artemis driving cycles [2]. To match various situations of the everyday life, realistic boundary conditions are determined by five starting times. The corresponding weather conditions are obtained and five weather profiles for every meteorological season including the ambient temperature, solar flux and humidity are considered. By using a complete FCEV simulation model, a realistic energy consumptions is simulated and the impact of different climate conditions as well as driving behaviors is investigated. As a result, a significant influence of the auxiliary load on the overall energy consumption is detected and the need to consider the overall energy demand is demonstrated.